PEMANFAATAN APLIKASI SISTEM INFORMASI KEARSIPAN DINAMIS TERINTEGRASI (SRIKANDI) DALAM PENGELOLAAN ARSIP DINAMIS DI DINAS ARSIP DAN PERPUSTAKAAN DAERAH KABUPATEN BULELENG: - - Ni Made Ayu Andriyani (ACARYA PUSTAKA, 2025)
The aims of this research are; (1) To find out why the Regional Archives and Library Service (DAPD) of Buleleng Regency uses the SRIKANDI Application, (2) To find out how the SRIKANDI Application is implemented in archival management, especially dynamic archives. This research uses a qualitative descriptive research method and the technique for determining informants uses purposive sampling. The author chose the research location, namely the Regional Archives and Library Service (DAPD) of Buleleng Regency. In this research, researchers used observation techniques, in-depth interview techniques, and document study techniques to collect data to obtain concrete data. From the research results obtained, the researcher found that there were several factors that the Regional Archives and Library Service (DAPD) of Buleleng Regency chose to use the SRIKANDI application for dynamic archive management and there was the use of other archive applications before the SRIKANDI application. There is also an implementation of the SRIKANDI application which is used in dynamic archive management which is experienced by archivists, such as in the stages of the archive management process through the SRIKANDI application, there is an official document menu, settings menu, reference master menu, file list and file submission. Apart from that, the benefits of using the SRIKANDI application for archivists as well as the obstacles and solutions found in operating the SRIKANDI application.